Tricky partners: native plants show stronger interaction preferences than their exotic counterparts. Issue 2 (23rd December 2020) - Coux, Camille; Donoso, Isabel; Tylianakis, Jason M.; García, Daniel; Martínez, Daniel; Dehling, D. Matthias; Stouffer, Daniel B.
Abstract: In ecological networks, neutral predictions suggest that species' interaction frequencies are proportional to their relative abundances. Deviations from neutral predictions thus correspond to interaction preferences (when positive) or avoidances (when negative), driven by nonneutral (e.g., niche‐based) processes. Exotic species interact with many partners with which they have not coevolved, and it remains unclear whether this systematically influences the strength of neutral processes on interactions, and how these interaction‐level differences scale up to entire networks. To fill this gap, we compared interactions between plants and frugivorous birds at nine forest sites in New Zealand varying in the relative abundance and composition of native and exotic species, with independently sampled data on bird and plant abundances from the same sites. We tested if the strength and direction of interaction preferences differed between native and exotic species. We further evaluated whether the performance of neutral predictions at the site level was predicted by the proportion of exotic interactions in each network from both bird and plant perspectives, and the species composition in each site. We found that interactions involving native plants deviated more strongly from neutral predictions than did interactions involving exotics. This "pickiness" of native plants could be detrimental in a context of global biotic homogenization where they could be increasingly exposed to novel interactions with neutrally interacting mutualists. However, the realization of only a subset of interactions in different sites compensated for the neutrality of interactions involving exotics, so that neutral predictions for whole networks did not change systematically with the proportion of exotic species or species composition. Therefore, the neutral and niche processes that underpin individual interactions may not scale up to entire networks. This shows that seemingly simplistic neutral assumptions entail complex processes and can provide valuable understanding of community assembly or invasion dynamics.